2008
DOI: 10.3797/scipharm.0803-16
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Antioxidant Effect of Pisonia aculeata L. against CCl4-Induced Hepatic Damage in Rats

Abstract: Ethanol extract of Pisonia aculeata (EPA) was evaluated for hepatoprotective and antioxidant activities in rats. The plant extract (250 and 500 mg/kg, p.o.) showed a remarkable hepatoprotective and antioxidant activity against carbon tetrachloride (CCl 4) -induced hepatotoxicity as judged from the serum marker enzymes and antioxidant levels in were compared with respective control. Results indicate the hepatoprotective and antioxidant properties of P. aculeata against CCl 4 -induced hepatotoxicity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…Palanivel et al (2008) also noted a decrease in serum bilirubin following the administration of an alcohol extract of Pisonia aculeata and silymarin in rats receiving a hepatotoxic compound daily for 10 days. This compound is based on carbon tetrachloride, and resulted in a loss of membrane integrity of hepatocytes and liver cell function.…”
Section: Blood Parametersmentioning
confidence: 99%
“…Palanivel et al (2008) also noted a decrease in serum bilirubin following the administration of an alcohol extract of Pisonia aculeata and silymarin in rats receiving a hepatotoxic compound daily for 10 days. This compound is based on carbon tetrachloride, and resulted in a loss of membrane integrity of hepatocytes and liver cell function.…”
Section: Blood Parametersmentioning
confidence: 99%
“…Decreased levels of GSH are associated with an enhanced lipid peroxidation in CCl4 treated rats, which in turn gives rise to other products like malondialdehyde that extensively causes membrane damage. 37 The present study demonstrated that both the AVU and Silymarin pretreated groups significantly reduced the oxidative stress by recovering the decreased activities of SOD, CAT, GSH and reducing the levels of malondialdehyde in CCl4-induced acute liver injury. The anti-oxidant activity was higher with test group administered AVU at a dose of 400mg/kg body weight when compared to 200 mg/kg body weight.…”
Section: Vein (10x) B) Ccl4 Treated Group Rats Show Steatosis Centrmentioning
confidence: 73%
“…Gupta et al (2012) investigated presence of triterpenoides, saponins, tannins and flavonoids from stem bark. For acute oral toxicity studies, extract treated animals were observed for mortality up to 72 h. Based on the results, the treatment byextract was not produced any mortality up to 2000 mg/kg body weight in rats (Palanivel et al, 2008).…”
Section: Phytochemical and Safety Studiesmentioning
confidence: 99%